Chiteki Zaisan Kôtô Saibansho, Das Obergericht für geistiges Eigentum in Tokyo – Neue Impulse für die praktische Durchsetzung technischer Schutzrechte in Japan - Beyerlein, Thorsten (Zeitschrift für Japanisches Recht, 2006)
Since April 1, 2005, the so-called “Intellectual Property High Court” (Chiteki Zaisan Kôtô Saibansho) has existed as a part of the High Court of Tokyo with a special focus on intellectual property. The aim of the creation of this court was to concentrate and increase the competence of the jurisdiction, particularly in questions of technical intellectual property rights. The Intellectual Property High Court is in particular responsible for complaints against decisions of the Japanese Patent Office and for appeals in civil cases relating to patent rights, utility model rights, semiconductor protection rights, and copyrights for computer programs – consequently for all technology-related civil disputes. By concentrating jurisdiction, the hope is that uniformity in case law regarding “technical intellectual property rights” will be established prior to the Supreme Court of Japan, at the Intellectual Property High Court. Staffed with legal and scientific personnel and temporarily appointed experts, the court’s competence regarding technical issues will be increased. Legal circles have greeted the creation of an Intellectual Property High Court with approval so far. In particular, the endeavor to shorten the length of litigation raises great expectations.